Ant community of an Acacia mangium forest in Indonesian Borneo - Helms I.V., Jackson A.; Helms, Sara M.; Fawzi, Nurul Ihsan; Tarjudin,; Xaverius, Fransiscus (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
The exotic timber tree Acacia mangium often colonizes areas of Borneo where native forests have been cleared for agriculture. To assess the biodiversity value of this novel habitat, we surveyed the ant community of a naturalized A. mangium forest on the border of Gunung Palung National Park in West Kalimantan, Indonesia. We documented 33 species from 18 genera and four subfamilies. The invasive yellow crazy ant (Anoplolepis gracilipes) dominated the assemblage, making up 85% of pitfall trapped individuals and 28% of those sifted from leaf litter. Nevertheless, A. mangium forest harbored fewer invasive species than nearby urban land, and may serve as an effective buffer around protected areas.